Expanding Our View: Demographic, Behavioral, and Contextual Factors in College Sexual Victimization - Rogers, Sarah (Journal of interpersonal violence, 2021)
Despite efforts on some college campuses to address the issue of sexual victimization, the numbers have not changed much over the last four decades. The purpose of this study is to examine how demographic, contextual, and behavioral factors influence sexual victimization on college campuses. Using data from the Fall 2011 National College Health Assessment/American College Health Association survey, we examine three hypotheses: (1) contextual factors will have a greater effect on the likelihood of victimization than behavioral factors; (2) demographic factors will have a greater effect on the likelihood of victimization than behavioral factors; and (3) contextual factors for men will have a greater effect than contextual factors for women. While previous studies have tackled portions of these larger objectives, few studies have focused on all three sets of factors of analysis simultaneously. Overall, we find that behavioral factors predict sexual victimization better than either demographic or contextual factors for both men and women. However, we also find that some contextual factors are significant, including variables not generally discussed in the literature, such as perception of typical student behaviors and dissemination of violence prevention programming and information. In addition, we add to the literature by showing how demographic, behavioral, and contextual factors of sexual victimization vary in significance for men and women. These findings support the calls for more sexual violence prevention programming on college campuses that is more intersectional and addresses the issue of sexual violence based on the knowledge we have gained about individual, interactional, and institutional factors that contribute to this problem.